2016
DOI: 10.1111/joa.12451
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and postural sexual dimorphism of the lumbar spine facilitates greater lordosis in females

Abstract: Previous work suggests females are evolutionarily adapted to have greater lumbar lordosis than males to aid in pregnancy load-bearing, but no consensus exists. To explore further sex-differences in the lumbar spine, and to understand contradictions in the literature, we conducted a cross-sectional retrospective study of sex-differences in lumbar spine morphology and sacral orientation. In addition, our sample includes data for separate standing and supine samples of males and females to examine potential sex-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 67 publications
2
40
0
Order By: Relevance
“…While the shape of the hips may be less affected between standing and lying, the shape of the spine changes measurably on going from standing to supine. This conclusion is supported by a recent study of 200 individuals which found a significantly larger lordosis angle in women than men while standing but not while lying supine (Bailey et al 2016). Although in previous studies we showed that an element of an intrinsic shape can still be identified between these postures (Meakin et al 2009), more associations between joint shapes may be evident in the natural weight-bearing position.…”
Section: Sm8supporting
confidence: 83%
See 2 more Smart Citations
“…While the shape of the hips may be less affected between standing and lying, the shape of the spine changes measurably on going from standing to supine. This conclusion is supported by a recent study of 200 individuals which found a significantly larger lordosis angle in women than men while standing but not while lying supine (Bailey et al 2016). Although in previous studies we showed that an element of an intrinsic shape can still be identified between these postures (Meakin et al 2009), more associations between joint shapes may be evident in the natural weight-bearing position.…”
Section: Sm8supporting
confidence: 83%
“…This conclusion is supported by a recent study of 200 individuals which found a significantly larger lordosis angle in women than men while standing but not while lying supine (Bailey et al. ). Although in previous studies we showed that an element of an intrinsic shape can still be identified between these postures (Meakin et al.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…With improvements in advanced imaging techniques, HLD has been increasingly recognized in symptomatic and asymptomatic individuals 2) . Pre-vious work suggests lumbar lordosis, representative of lordotic curvature between L1 and S1, was 7.3° greater in females than males when standing 1) . Additionally, the sacral slope was greater in females than males, when standing.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the structural and functional bases for lordosis variation is a challenge because the alignment of the spine and balance of the upper body are influenced by several inter‐related factors. For instance, LL is mechanically linked to other spinal postural parameters such as thoracic kyphosis, pelvic orientation, and sacral incidence (Bailey et al, ; Vialle et al, ). Several non‐mechanical factors have also been shown to be associated with LL including individual factors such as age, sex, height, and body mass; genetic factors influencing heritability; and environmental factors such as occupational loading, athletic training, and physical fitness (for review, see Been and Kalichman, ).…”
Section: Introductionmentioning
confidence: 99%